Phosphogypsum-based road base material and preparation method thereof
By introducing raw materials such as magnesium oxide, magnesium chloride and polymer nanocomposites into the phosphogypsum-based road base materials, the problems of low strength and poor water stability are solved, and efficient utilization of phosphogypsum resources and environmentally friendly road bases are achieved. Material preparation.
Patent Information
- Application Number
- CN202411331307.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, when using phosphogypsum to prepare road base materials, there are problems of low strength and poor water stability, and most technologies require the use of gravel or large amounts of cement, resulting in waste of resources and environmental pollution.
Phosphogypsum, magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, sodium bicarbonate and polymer nanocomposite materials and modifiers are used as raw materials to prepare phosphogypsum-based road base materials through specific mixing and treatment methods, and use modifications The agent and polymer nanocomposites improve the compactness and water stability of the gelled phase.
It significantly improves the unbounded compressive strength and water stability of the phosphogypsum-based road base material, and the utilization rate of phosphogypsum reaches 84-92%, and there is no need to use graded gravel, which reduces the dependence on sand and gravel materials, and has significant Economic, social and environmental benefits.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of road engineering construction, and in particular to a phosphogypsum-based road base material and a preparation method thereof. Background Art
[0002] Phosphogypsum is an industrial byproduct of the production of phosphoric acid and phosphate fertilizers. About 5 tons of phosphogypsum are produced for every ton of phosphoric acid produced. At present, the main way to deal with phosphogypsum is to pile it up, and the resource utilization rate is not high. The global stockpile of phosphogypsum has exceeded 6 billion tons and is still growing. Phosphogypsum contains phosphoric acid, sulfuric acid, hydrofluoric acid, and heavy metal pollutants such as arsenic, cadmium, and mercury. Large-scale stockpiling not only occupies land, but also pollutes the surrounding groundwater and soil. The harmless treatment and resource utilization of phosphogypsum have become a research hotspot in recent years.
[0003] In addition, the traditional road base construction material is mainly cement-stabilized gravel. Cement-stabilized gravel uses graded gravel as aggregate, uses a certain amount of cement and sufficient mortar volume to fill the gaps in the aggregate, and is spread and compacted according to the principle of interlocking and extrusion. It has high strength, impermeability and frost resistance. However, cement-stabilized gravel consumes a large amount of gravel and cement. The methods of quarrying in mountains and digging in rivers have irreversible effects on resources, environment and ecology, causing shortages or depletion of building materials in many areas, and also causing a series of problems such as vegetation reduction, soil erosion, and environmental deterioration. In addition, the production process of cement produces a large amount of carbon dioxide. Therefore, the use of phosphogypsum to prepare road base materials instead of traditional cement-stabilized gravel can not only solve the problem of resource utilization of phosphogypsum, but also save a large amount of gravel and cement, and has broad application prospects and significant social, economic and environmental benefits.
[0004] Patent CN 104909695 B discloses a phosphogypsum hydraulic road base, road base material and its preparation method. This technology uses phosphogypsum as the main raw material, cement as the gelling material, and a hydraulic curing agent composed of elastic styrene-acrylic emulsion, nano-aluminum sol, and nano-silica sol as an additive. After mixing and rolling, the road base material is obtained, and its 7d and 28d unconfined compressive strength can reach 2.68MPa and 8MPa or more. However, the patent does not evaluate its water stability.
[0005] Patent CN 106517979 B uses 30-40% phosphogypsum to replace graded crushed stone, uses cement as the gelling material, and adds polyacrylonitrile fiber, polyvinyl alcohol, cationic polyacrylamide and polyurethane to improve its crack resistance.
[0006] Patent CN 108275931 B provides a modified phosphogypsum material, which uses modified phosphogypsum, red mud, fly ash, alum slag, cement, anionic silicone surfactant, curing agent, stearic acid-polystyrene emulsion, hydrophobic modifier, and impermeability agent to produce road materials, which can replace traditional road base and road water-stabilizing layer. The formed road layer has strong crack resistance, is not easy to corrode, and has a long service life. This technology requires aging and calcining of phosphogypsum, and the preparation technology is cumbersome. The calcination process consumes additional energy and is not environmentally friendly. Patent CN 117125910 A also requires aging treatment, and the production process is relatively cumbersome.
[0007] Patents CN 113754398 B, CN 111848083 B, CN 111499324 B, CN 115521125 A, etc. use phosphogypsum and graded crushed stone to prepare cement-stabilized crushed stone materials, which have good unconfined compressive strength. However, such technologies still require the use of some crushed stone, and the amount of phosphogypsum used is not large, so it is difficult to consume a large amount of phosphogypsum.
[0008] Patent CN 117361979 A discloses a technology for preparing road base materials using calcined phosphogypsum, natural coarse aggregate, natural fine aggregate, silicate cement, modifier, EVA emulsion, PU emulsion and water. This technology uses the organic gelling effect of EVA and PU emulsion to limit the shrinkage of cement mortar, effectively reducing the cracking problem caused by shrinkage and temperature shrinkage of road base materials. However, this technology still requires the use of a large amount of sand and gravel aggregates, and phosphogypsum needs to be calcined before use, which is not economical and environmentally friendly.
[0009] Patent CN 116768588 B discloses a method for preparing phosphogypsum solidified sludge for road materials. The road materials are prepared using phosphogypsum, sludge, silicon slag, cement, and curing agent, and the phosphogypsum is wrapped and agglomerated using sludge. The technology is simple in production process, does not require high-temperature heating, has low energy consumption, and has low production cost. However, the water stability of phosphogypsum and sludge is poor, and the technology does not process and evaluate their water stability.
[0010] Patent CN 116789389 A discloses a cement-based phosphogypsum curing agent and a cement-based roadbed material using the same. The technology uses sodium polyacrylate, polyvinyl alcohol, 1,2,3,4-butanetetracarboxylic acid, water reducer, polyethylene glycol, calcium lignin sulfonate, and silane coupling agent to prepare the curing agent, and combines cement to cure the phosphogypsum to prepare the cement-based roadbed material. The technology greatly improves the water stability of the cured phosphogypsum and has a higher strength, but the technology requires a large amount of cement to cure the phosphogypsum, which is not environmentally friendly.
[0011] Although the above patented technologies use phosphogypsum to prepare road base materials and have high unconfined compressive strength, most of them require crushed stone as aggregate or cement as cementing material. Although some patented technologies can use phosphogypsum as the main raw material to prepare road base materials, there are still problems such as the need to use cement as the main cementing material or the complicated preparation process, and most patented technologies do not evaluate the water stability of the prepared road base materials. Summary of the invention
[0012] Purpose of the invention: The first purpose of the present invention is to provide a phosphogypsum-based road base material which does not require the use of crushed stone or more cement and has improved strength and water stability properties; the second purpose of the present invention is to provide a method for preparing the phosphogypsum-based road base material.
[0013] Technical solution: The phosphogypsum-based road base material of the present invention comprises the following raw materials, by mass percentage: 84-92% of phosphogypsum, 4-8% of magnesium oxide, 1-3% of magnesium chloride, 1-2% of mineral powder, 0.5-1% of cement, 0.25-0.5% of gypsum, 0.25-0.5% of sodium bicarbonate, 0.25-0.5% of polymer nanocomposite material and 0.25-0.5% of modifier; wherein the modifier comprises ferrous sulfate and graphene oxide; the polymer nanocomposite material comprises nano silicon dioxide and acrylic emulsion.
[0014] Preferably, the mass ratio of ferrous sulfate to graphene oxide in the modifier is 1:1-2.
[0015] Preferably, in the polymer nanocomposite material, the mass ratio of nano-silicon dioxide to acrylic emulsion is 1:5-10.
[0016] Preferably, the magnesium oxide is light-burned magnesium oxide with an active magnesium oxide content of not less than 80%; the calcination temperature of the light-burned magnesium chloride is 850-900° C., the calcination constant temperature time is 0.5-1.0 hour, and the particle size is not greater than 100 mesh.
[0017] The magnesium chloride is anhydrous magnesium chloride or magnesium chloride hexahydrate.
[0018] Preferably, the phosphogypsum is solid waste generated by a wet phosphoric acid process, the main component of which is dihydrate gypsum with a moisture content of 15-20%.
[0019] Preferably, the gypsum is hemihydrate gypsum with a calcium sulfate content greater than 80%.
[0020] The mineral powder is S95 mineral powder with a specific surface area greater than 550m 2 / kg.
[0021] The cement is P.O42.5 ordinary Portland cement.
[0022] The method for preparing the phosphogypsum-based road base material of the present invention is characterized by comprising the following steps:
[0023] (1) adjusting the moisture content of phosphogypsum and then crushing it;
[0024] (2) weighing magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, and sodium bicarbonate in proportion, mixing them evenly, and preparing a curing agent;
[0025] (3) mixing the polymer nanocomposite material and the modifier uniformly, then diluting the mixture with water by 30 to 50 times and mixing the mixture uniformly to obtain a mixed dilution of the polymer nanocomposite material and the modifier;
[0026] (4) spraying the mixed diluted solution of the polymer nanocomposite material and the modifier prepared in step (3) onto the surface of the phosphogypsum treated in step (1), and mixing them uniformly to obtain a mixture;
[0027] (5) adding the curing agent prepared in step (2) to the mixture prepared in step (4) and mixing them evenly to obtain a phosphogypsum-based road base material.
[0028] Preferably, in step (1), the method for adjusting the moisture content of the phosphogypsum is: adjusting the moisture content of the phosphogypsum produced by the wet phosphoric acid process by drying or adding water, so that the moisture content reaches 15-20%. The crushing process is: crushing the phosphogypsum with the required moisture content by using a rotary tiller / BMW machine or a crusher until the maximum particle size is less than 40 mm.
[0029] Preferably, in step (2), the uniform mixing is carried out by mechanical stirring for 3 to 4 minutes at a stirring rate of 30 to 60 r / min.
[0030] Preferably, in step (3), the uniform mixing is performed by stirring with a high-speed stirrer.
[0031] Preferably, in step (4) or (5), the uniform mixing is performed by using a rotary tiller or a BMW tiller for 3 to 4 times.
[0032] Preferably, the preparation method of the modifier comprises the following steps:
[0033] (1) adding graphene oxide to deionized water and dispersing the graphene oxide uniformly to form a graphene oxide dispersion;
[0034] (2) Add ferrous sulfate to the graphene oxide dispersion of step (1), mix well, and obtain a modifier.
[0035] In step (1), graphene oxide is first added to deionized water to disperse the graphene oxide. Preferably, the amount of water added is generally 100 to 200 times the mass of the graphene oxide.
[0036] Preferably, the method for preparing the polymer nanocomposite material comprises the following steps:
[0037] (1) adding nano-silicon dioxide into deionized water and dispersing the nano-silicon dioxide uniformly to form a nano-silicon dioxide dispersion;
[0038] (2) Add the nano-silicon dioxide dispersion into the acrylic emulsion and mix them evenly to obtain a polymer nano-composite material.
[0039] In step (1), nano silicon dioxide is first added to water to disperse the silicon dioxide, which helps to mix it evenly with the acrylic emulsion and avoid agglomeration of the silicon dioxide. Preferably, the amount of water added is generally 10 to 15 times the mass of the silicon dioxide.
[0040] Invention mechanism:
[0041] The present invention introduces a modifier and a polymer nanocomposite material into phosphogypsum. The ferrous sulfite and graphene oxide in the modifier play an important role. Under the catalytic action of ferrous sulfate, magnesium oxide, magnesium chloride and water in the phosphogypsum react together to form a gelled phase 5Mg(OH)2·MgCl2·8H2O phase (5-phase) product. The 5-phase product of the gelled phase is denser and has stronger water stability than the traditional stick-shaped 5-phase product. The 5-phase product of the gelled phase gathers at the contact points of the phosphogypsum particles, cements the phosphogypsum particles, and forms strength for the phosphogypsum. The residual phosphoric acid in the phosphogypsum reacts with magnesium oxide to form an insoluble magnesium phosphate precipitate that covers the surface of the 5-phase material, preventing the 5-phase product from contacting with water and decomposing, thereby further improving water stability. The sodium bicarbonate in the curing agent reacts with the magnesium hydroxide produced by the hydration of magnesium oxide and the 5-phase product to form hydrocarbite, which further cements the phosphogypsum particles to improve strength and improve water stability. In addition, graphene oxide has a high specific surface area and abundant oxidized groups, which can interact with calcium sulfate in phosphogypsum through hydrogen bonds and van der Waals forces to form a strong network structure, thereby significantly enhancing the mechanical properties and water stability of phosphogypsum.
[0042] In polymer nanocomposites, the carboxyl groups in acrylic acid can increase the surface energy of phosphogypsum and significantly improve the interfacial properties of phosphogypsum particles. On the one hand, it can enhance the interaction between phosphogypsum particles and the 5-phase products, improve the interfacial strength, and prevent the interface damage between phosphogypsum particles and the 5-phase products. On the other hand, the high specific surface area of nano-silicon dioxide in polymer nanocomposites leads to the agglomeration effect of the 5-phase products, making the 5-phase products easily aggregate at the contact points of phosphogypsum particles, thereby improving the cementation efficiency. In addition, nano-silicon dioxide reacts with magnesium oxide and calcium sulfate in phosphogypsum to generate hydrated magnesium silicate and hydrated calcium silicate gel covering the 5-phase surface, and forms a composite water-proof layer with magnesium phosphate and hydrocarburite to prevent the 5-phase products from contacting water and improve water stability.
[0043] In addition, the carboxyl group of acrylic acid reacts with the iron ions in ferrous sulfate to form insoluble acrylic acid iron salts. The acrylic acid iron salts cover the surface of the 5-phase product to prevent the 5-phase product from contacting water, which is also important for improving the water stability of phosphogypsum.
[0044] The mineral powder undergoes vitreous disintegration in the alkaline environment provided by magnesium oxide and cement, and reacts with gypsum to form cementitious products such as CSH gel and calcium sulfonate. On the one hand, CSH gel and calcium sulfonate have excellent cementing effects, and can be used together with the five-phase products to cement the phosphogypsum particles to improve strength; on the other hand, calcium sulfonate has good volume expansion characteristics, which can fill the pores between the phosphogypsum particles, improve the density, and thus improve the strength and water stability. The content of expansion components such as mineral powder and gypsum is designed according to the initial compaction of phosphogypsum to fill the pores and make up for the low strength and poor water stability caused by insufficient compaction.
[0045] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0046] (1) Through the combined action of polymer nanocomposites and modifiers, based on a series of principles such as improving the surface properties of phosphogypsum particles, optimizing the morphology and aggregation position of the five-phase products, and forming a composite waterproof layer, the cementation efficiency of the five-phase products was improved, fundamentally solving the technical problems of low strength and poor water stability of phosphogypsum;
[0047] (2) Modifiers and polymer nanocomposites are introduced into phosphogypsum, and phosphogypsum is used as the main raw material to prepare road base materials. The utilization rate of phosphogypsum can reach 84-92%, and there is no need to use graded crushed stone, which reduces the dependence of road construction on crushed stone. At the same time, a large amount of phosphogypsum is consumed, which not only solves the problem of phosphogypsum resource utilization, but also saves a large amount of sand and gravel materials for road construction, with significant economic, social and environmental benefits.
[0048] (3) Different from the cementitious materials in the prior art which use cement as the main component, the present invention uses magnesium oxide and magnesium chloride as the main solidifying materials to produce phosphogypsum-based road base materials, wherein the calcination temperature of magnesium oxide is much lower than that of ordinary Portland cement, so the energy consumption is low and the carbon dioxide emission is low. Magnesium chloride is a by-product of seawater salt production and has a good environmental effect. Meanwhile, the residual phosphoric acid in phosphogypsum can improve the water stability of the five-phase product. The advantages of phosphogypsum, magnesium oxide and magnesium chloride complement each other.
[0049] (4) According to the compaction degree of phosphogypsum, the content of expansive components such as mineral powder and gypsum is adjusted to effectively fill the pores in the phosphogypsum-based road base material, make up for the low strength and poor water stability caused by low compaction degree, and ensure the strength and water stability of the phosphogypsum-based road base material. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described below in conjunction with embodiments.
[0051] Example 1
[0052] The phosphogypsum-based road base material of the present invention comprises the following raw materials, by mass percentage: 88% of phosphogypsum, 7% of magnesium oxide, 2% of magnesium chloride, 1% of mineral powder, 0.5% of cement, 0.25% of gypsum, 0.25% of sodium bicarbonate, 0.5% of polymer nanocomposite material and 0.5% of modifier.
[0053] The modifier is composed of ferrous sulfate and graphene oxide in a 1:1 ratio. The graphene oxide is graphene oxide.
[0054] In the polymer nanocomposite material, the mass ratio of nano silicon dioxide to acrylic emulsion is 1: 10. Acrylic emulsion is purchased from Jinan Xinwo Chemical Co., Ltd. and is a slightly transparent milky white liquid with a solid content of 50%.
[0055] The phosphogypsum has a moisture content of 16.5% and a compactness of 98%.
[0056] The magnesium oxide is light-burned magnesium oxide with an active magnesium oxide content of 81.3%, a calcination temperature of 850-900° C., a calcination constant temperature time of 0.5-1.0 hour, and a particle size of no more than 100 meshes.
[0057] The magnesium chloride is anhydrous magnesium chloride.
[0058] The mineral powder is S95 mineral powder with a specific surface area of 560m 2 / kg.
[0059] The cement is P.O42.5 ordinary Portland cement.
[0060] The gypsum is hemihydrate gypsum with a calcium sulfate content of 80.5%.
[0061] In the polymer nanocomposite material, the mass ratio of nano silicon dioxide, deionized water and acrylic emulsion is 1:10:10, and the preparation method is as follows:
[0062] (1) adding nano-silicon dioxide into deionized water and dispersing it by ultrasonic for 30 minutes to form a nano-silicon dioxide dispersion;
[0063] (2) Slowly add the nano-silica dispersion into the acrylic emulsion and stir for 10 minutes using a high-speed stirrer to ensure that the polymer emulsion and the mixed solution are evenly combined to obtain a polymer nano-composite material.
[0064] In the modifier, the mass ratio of graphene oxide, deionized water and ferrous sulfate is 1:200:1, and the preparation method is as follows:
[0065] (1) adding graphene oxide to deionized water and dispersing it using ultrasound for 30 minutes to form a graphene oxide dispersion;
[0066] (2) Add ferrous sulfate to the graphene oxide dispersion and stir the mixture for 10 minutes using a high-speed stirrer to obtain a modifier.
[0067] The present invention also provides a method for preparing a phosphogypsum-based road base material, which specifically comprises the following steps:
[0068] (1) adjusting the moisture content of the phosphogypsum produced by the wet phosphoric acid process by drying or adding water to make its moisture content reach 16.5%; then crushing the phosphogypsum with the moisture content meeting the requirements by using a JC-FS-1 soil continuous crusher until the maximum particle size is less than 40 mm;
[0069] (2) magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, and sodium bicarbonate are weighed in proportion, and stirred mechanically for 3 to 4 minutes at a stirring rate of 30 to 60 r / min to prepare a curing agent;
[0070] (3) mixing the polymer nanocomposite material and the modifier, stirring the mixture with a high-speed stirrer for 5 minutes, then diluting the mixture with water by 30 times and stirring the mixture with a high-speed stirrer for 10 minutes to obtain a mixed dilution of the polymer nanocomposite material and the modifier;
[0071] (4) spraying the mixed diluted solution of the polymer nanocomposite material and the modifier prepared in (3) onto the surface of the phosphogypsum prepared in (1), and performing rotary tillage and mixing using a rotary tiller for 3 to 4 times to obtain a mixture;
[0072] (5) adding the curing agent prepared in (2) to the mixture prepared in (4), and using a rotary tiller to perform rotary tillage and mixing, the rotary tillage is repeated 3 to 4 times to obtain a phosphogypsum-based road base material.
[0073] Example 2
[0074] The phosphogypsum-based road base material of the present invention comprises the following raw materials by mass percentage: 84% phosphogypsum, 8% magnesium oxide, 3% magnesium chloride, 2% mineral powder, 1.0% cement, 0.5% gypsum, 0.5% sodium bicarbonate, 0.5% polymer nanocomposite material and 0.5% modifier. The modifier is a composite of ferrous sulfate and graphene oxide in a ratio of 1:2. The phosphogypsum has a water content of 16.5% and a compactness of 98%.
[0075] Example 3
[0076] The phosphogypsum-based road base material of the present invention comprises the following raw materials by mass percentage: 92% phosphogypsum, 4% magnesium oxide, 1.5% magnesium chloride, 1% mineral powder, 0.5% cement, 0.25% gypsum, 0.25% sodium bicarbonate, 0.25% polymer nanocomposite material and 0.25% modifier. The modifier is a composite of ferrous sulfate and graphene oxide in a ratio of 1:1. In the polymer nanocomposite material, the mass ratio of nano silicon dioxide to acrylic emulsion is 1:5. The phosphogypsum has a water content of 16.5% and a compactness of 98%.
[0077] Example 4
[0078] The phosphogypsum-based road base material of the present invention comprises the following raw materials by mass percentage: 88% phosphogypsum, 6.5% magnesium oxide, 2% magnesium chloride, 1.25% mineral powder, 0.5% cement, 0.5% gypsum, 0.25% sodium bicarbonate, 0.5% polymer nanocomposite material and 0.5% modifier. The modifier is a composite of ferrous sulfate and graphene oxide in a ratio of 1:1. The phosphogypsum has a water content of 16.5% and a compactness of 96%.
[0079] Comparative Example 1
[0080] The phosphogypsum-based road base material is composed of the following raw materials in percentage by mass: 88% phosphogypsum and 12% cement, wherein the phosphogypsum has a water content of 16.5% and a compaction degree of 98%. The selected raw materials and preparation method are the same as those in Example 1.
[0081] Comparative Example 2
[0082] The phosphogypsum-based road base material is composed of the following raw materials in percentage by mass: 88% phosphogypsum, 7.5% magnesium oxide, 2.75% magnesium chloride, 0.5% cement, 0.25% sodium bicarbonate, 0.5% polymer nanocomposite material and 0.5% modifier. The modifier is a composite of ferrous sulfate and graphene oxide in a ratio of 1:1. The phosphogypsum has a water content of 16.5% and a compaction degree of 96%. The selected raw materials and preparation method are the same as those in Example 1.
[0083] Comparative Example 3
[0084] The phosphogypsum-based road base material is composed of the following raw materials in mass percentage: 88% phosphogypsum, 7% magnesium oxide, 2% magnesium chloride, 1% mineral powder, 0.75% cement, 0.25% gypsum, 0.5% polymer nanocomposite material and 0.5% modifier. The modifier is a composite of ferrous sulfate and graphene oxide in a ratio of 1:1. The phosphogypsum has a moisture content of 16.5% and a compactness of 98%.
[0085] Comparative Example 4
[0086] The phosphogypsum-based road base material is composed of the following raw materials in percentage by mass: 88% phosphogypsum, 8% magnesium oxide, and 4% magnesium chloride. The phosphogypsum has a water content of 16.5% and a compactness of 98%. The selected raw materials and preparation method are the same as those in Example 1.
[0087] Comparative Example 5
[0088] The phosphogypsum-based road base material is composed of the following raw materials in mass percentage: 88% phosphogypsum, 7.5% magnesium oxide, 2% magnesium chloride, 1% mineral powder, 0.5% cement, 0.25% gypsum, 0.25% sodium bicarbonate and 0.5% modifier. The modifier is a composite of ferrous sulfate and graphene oxide in a ratio of 1:1. The phosphogypsum has a moisture content of 16.5% and a compaction degree of 98%. The selected raw materials and preparation method are the same as those in Example 1.
[0089] Comparative Example 6
[0090] The phosphogypsum-based road base material is composed of the following raw materials in percentage by mass: 88% phosphogypsum, 7.5% magnesium oxide, 2% magnesium chloride, 1% mineral powder, 0.5% cement, 0.25% gypsum, 0.25% sodium bicarbonate, 0.5% polymer nanocomposite material, and has a compaction degree of 98%. The selected raw materials and preparation method are the same as those in Example 1.
[0091] Comparative Example 7
[0092] The same as Example 1, except that the phosphogypsum-based road base material is prepared by the following steps:
[0093] (1) The moisture content of the phosphogypsum produced by the wet phosphoric acid process is adjusted by drying or adding water to reach 16.5%. The phosphogypsum with the required moisture content is crushed by a JC-FS-1 soil continuous crusher until the maximum particle size is less than 40 mm;
[0094] (2) Magnesium oxide, magnesium chloride, mineral powder, cement, gypsum and sodium bicarbonate are weighed in proportion, and stirred for 4 minutes by mechanical stirring at a stirring rate of 30 to 60 r / min to prepare a curing agent.
[0095] (3) adding the curing agent prepared in (2) into the phosphogypsum obtained in (1) in proportion, and using a rotary tiller to perform rotary tillage and crushing, with the rotary tillage being repeated 3 to 4 times.
[0096] (4) The polymer nanocomposite material and the modifier are mixed, stirred for 5 minutes using a high-speed stirrer, and then diluted with water by 30 times and stirred for 10 minutes using a high-speed stirrer to obtain a mixed dilution of the polymer nanocomposite material and the modifier.
[0097] (5) Spraying the mixed diluted liquid of the polymer nanocomposite material and the modifier prepared in (4) onto the surface of the phosphogypsum prepared in (3) in proportion, and using a rotary tiller to perform rotary tillage and crushing, the rotary tillage is repeated 3 to 4 times to obtain a phosphogypsum-based road base material.
[0098] The unconfined compressive strength and water stability of the road base materials obtained in Examples 1 to 4 and Comparative Examples 1 to 7 were tested with reference to the test method of "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTGE51-2009). The results are shown in Table 1.
[0099] Table 1 Test results of embodiments and comparative examples
[0100]
[0101]
[0102] Through Examples 1 to 4, it can be found that the phosphogypsum-based road base material provided by the present invention can achieve a 7d unconfined compressive strength of 6.76 to 14.51 MPa and a 28d unconfined compressive strength of 9.64 to 18.65 MPa under the condition that the usage amount of phosphogypsum reaches 84% to 92%, and the water stability coefficient is ≥ 0.97, which is much higher than the requirements of the specifications for road base materials. It can be used to replace cement-stabilized crushed stone to prepare road base and subbase, which can not only remove a large amount of phosphogypsum, but also reduce the dependence of road construction on sand and gravel, and has significant environmental, economic and social benefits.
[0103] By comparing Examples 1 to 4 with Comparative Example 1, it is found that when only phosphogypsum and ordinary Portland cement are used to prepare the road base material without using the ratio disclosed in the present invention, the 7d unconfined compressive strength is only 1.71MPa, the 28d unconfined compressive strength is only 2.74MPa, and the water stability coefficient is only 0.62, which cannot meet the strength and water stability requirements of the road base and subbase. The ratio disclosed in the present invention is significantly better than the phosphogypsum-based road base material prepared by traditional ordinary Portland cement materials.
[0104] Comparing Examples 1 and 4 with Comparative Example 2, when mineral powder and gypsum are not added, the strength and water stability of Comparative Example 2 are significantly lower than those of Example 4 due to the lack of necessary expansion components in the curing agent to fill the pores. Although the compaction degree of Example 4 is lower than that of Example 2, due to the use of a reasonable amount of expansion components composed of mineral powder and gypsum in Example 4, the pores can be effectively filled, so that the 7d unconfined compressive strength in Example 4 is only 0.49MPa lower than that in Example 1, and the water stability coefficient is equivalent to that in Example 1; while the 7d unconfined compressive strength and water stability coefficient of Comparative Example 2 are 6.88MPa and 0.22 lower than those in Example 1, which are much higher than those in Example 4, indicating that the reasonable expansion components composed of mineral powder and gypsum significantly improve the strength and water stability of phosphogypsum-based road base materials.
[0105] In combination with Example 1 and Comparative Examples 3, 4, 5 and 6, it can be found that the use of magnesium oxide and magnesium chloride alone to solidify phosphogypsum to prepare phosphogypsum-based road base materials can achieve good unconfined compressive strength, but the water stability is poor and cannot meet the requirements of road base materials. The use of sodium bicarbonate, polymer nanocomposites and modifiers can all improve the unconfined compressive strength and water stability of phosphogypsum-based road base materials to a certain extent, but the improvement effect is limited. The improvement effect produced by the simultaneous use of sodium bicarbonate, polymer nanocomposites, modifiers, mineral powder, cement and gypsum provided by the present invention is better than the sum of the improvement effects produced by using any component alone, indicating that the magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, sodium bicarbonate, polymer nanocomposites and modifier component technical solutions provided by the present invention have functional mutual support.
[0106] By comparing Example 1 with Comparative Example 7, it can be found that when a curing agent composed of magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, and sodium bicarbonate is first mixed with phosphogypsum, and then a mixed dilution of a polymer nanocomposite material and a modifier is sprayed, the unconfined compressive strength and water stability of the prepared phosphogypsum-based road base material are much lower than the technical solution provided by the present invention. This is mainly because when a curing agent composed of magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, and sodium bicarbonate is first mixed with phosphogypsum, magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, sodium bicarbonate, and their products will be adsorbed on the surface of phosphogypsum particles, affecting the improvement of the interface characteristics of the polymer matrix and graphene oxide on the surface of the phosphogypsum particles, affecting the mechanical properties and water stability of the phosphogypsum-based road base material. It is shown that the preparation method of the phosphogypsum-based road base material provided by the present invention plays a vital role in ensuring the mechanical properties and water stability of the phosphogypsum-based road base material.
Claims
1. A phosphogypsum-based road base material, characterized in that: The invention comprises the following raw materials by mass percentage: 84-92% of phosphogypsum, 4-8% of magnesium oxide, 1-3% of magnesium chloride, 1-2% of mineral powder, 0.5-1% of cement, 0.25-0.5% of gypsum, 0.25-0.5% of sodium bicarbonate, 0.25-0.5% of polymer nanocomposite material and 0.25-0.5% of modifier; wherein the modifier comprises ferrous sulfate and graphene oxide; and the polymer nanocomposite material comprises nano silicon dioxide and acrylic emulsion.
2. The phosphogypsum-based road base material according to claim 1, characterized in that: The mass ratio of ferrous sulfate to graphene oxide in the modifier is 1:1-2.
3. The phosphogypsum-based road base material according to claim 1, characterized in that: In the polymer nanocomposite material, the mass ratio of nano silicon dioxide to acrylic emulsion is 1:5-10.
4. The phosphogypsum-based road base material according to claim 1, characterized in that: The magnesium oxide is light-burned magnesium oxide with an active magnesium oxide content of not less than 80%.
5. The phosphogypsum-based road base material according to claim 4, characterized in that: The calcination temperature of the light-burned magnesium oxide is 850-900° C., the calcination constant temperature time is 0.5-1.0 hour, and the particle size is not greater than 100 meshes.
6. The phosphogypsum-based road base material according to claim 1, characterized in that: The phosphogypsum is a solid waste produced by the wet phosphoric acid process, and its main component is dihydrate gypsum with a water content of 15-20%.
7. The phosphogypsum-based road base material according to claim 1, characterized in that: The gypsum is hemihydrate gypsum with a calcium sulfate content greater than 80%.
8. A method for preparing the phosphogypsum-based road base material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) adjusting the moisture content of phosphogypsum and then crushing it; (2) weighing magnesium oxide, magnesium chloride, mineral powder, cement, gypsum, and sodium bicarbonate in proportion, mixing them evenly, and preparing a curing agent; (3) mixing the polymer nanocomposite material and the modifier uniformly, then diluting the mixture with water by 30 to 50 times and mixing the mixture uniformly to obtain a mixed dilution of the polymer nanocomposite material and the modifier; (4) spraying the mixed diluted solution of the polymer nanocomposite material and the modifier prepared in step (3) onto the surface of the phosphogypsum treated in step (1), and mixing them uniformly to obtain a mixture; (5) adding the curing agent prepared in step (2) to the mixture prepared in step (4) and mixing them evenly to obtain a phosphogypsum-based road base material.
9. The method for preparing the phosphogypsum-based road base material according to claim 8, characterized in that: The preparation method of the modifier comprises the following steps: (1) adding graphene oxide to deionized water and dispersing the graphene oxide uniformly to form a graphene oxide dispersion; (2) Add ferrous sulfate to the graphene oxide dispersion of step (1), and mix well to obtain a modifier.
10. The method for preparing phosphogypsum-based road base material according to claim 8, characterized in that: The preparation method of the polymer nanocomposite material comprises the following steps: (1) adding nano-silicon dioxide into deionized water and dispersing the nano-silicon dioxide uniformly to form a nano-silicon dioxide dispersion; (2) Add the nano-silicon dioxide dispersion into the acrylic emulsion and mix them evenly to obtain a polymer nano-composite material.
Citation Information
Cited By
Water-resistant all-solid waste phosphogypsum road building material and preparation method thereof
CN121135342A
